2011
DOI: 10.1007/s00380-011-0169-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension on short- and long-term prognoses in patients with ST elevation myocardial infarction and without previously known diabetes

Abstract: Hypertension is well established as a risk factor for the development of atherosclerosis. Data on the impact of hypertension in patients with ST elevation myocardial infarction are so far inconsistent, and are mainly related to studies performed in the thrombolytic era. We assessed the impact of hypertension over the short and long term in 560 patients with ST elevation myocardial infarction (STEMI) and without previously known diabetes, all of whom were submitted to mechanical revascularization and consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In a recent study, Lazzeri et al [20] in a population of 560 STEMI patients without known diabetes, showed at a median follow-up of 32 months no impact of hypertension on mortality. This is the first study investigating the impact of hypertension on infarct size as evaluated by scintigraphic technique.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a recent study, Lazzeri et al [20] in a population of 560 STEMI patients without known diabetes, showed at a median follow-up of 32 months no impact of hypertension on mortality. This is the first study investigating the impact of hypertension on infarct size as evaluated by scintigraphic technique.…”
Section: Discussionmentioning
confidence: 95%
“…In a study by Majahalme et al [14], in-hospital and 6-month mortality in hypertensive and normotensive acute coronary syndrome (ACS) patients were similar, whereas the rate of recurrent angina, paroxysmal atrial fibrillation, and acute renal failure was higher among patients with hypertension. While the negative prognostic impact of hypertension after thrombolysis in patients STEMI, has been clearly demonstrated, and mainly due to higher rates of heart failure, stroke, cranial hemorrhage, and mortality [10][11][12][13][14][15][16], only a few studies [17][18][19][20] have assessed the impact of hypertension on outcome after primary angioplasty, which currently represents the best reperfusion strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parodi et al 35 found the 5-year mortality in patients with and without hypertension was comparable; however, patients with hypertension were at a higher risk of developing heart failure after STEMI. Lazzeri et al 36 assessed the influence of hypertension on the short-term and long-term outcome in 560 patients with STEMI submitted to mechanical revascularisation and found that a history of hypertension had no affect on either short-term or long-term mortality. Similar results were also found in Cecchi et al 's report 37.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension did not affect short-and long term mortality in patients with ST elevation myocardial infarction (STEMI) receiving PCI [2, 3]. However, hypertension was the only independent long-term predictor of mortality in patients with unstable angina (US) receiving coronary stenting [4].…”
Section: Introductionmentioning
confidence: 99%